Improving patient safety: we need to reduce hierarchy and empower junior doctors to speak up. (2nd July 2019) - Brennan, Peter A; Davidson, Mike
Abstract : Empowering doctors to speak up when they have concerns is essential to making our NHS safer, say Peter Brennan and Mike Davidson